Eco-Race Cilik: Adu Kecepatan dan Ketepatan Menyelamatkan Bumi, Edukasi Pemilahan Sampah Organik dan Anorganik bagi Anak Kelas III-IV Sekolah Dasar - Destira Ayu Permana; Inayah Adhani Khoirroni; Widya Tri Arianti; Nur Avifah Dwi Apriliani; Dhiyah Ulhaq Addinillah; Deskia Nur Ramadhani (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2026)
The waste problem is still an environmental issue that requires serious attention, especially regarding the low level of public awareness in sorting organic and inorganic waste at its source. Environmental education needs to be given from an early age to form attitudes and behavior that care for the environment in a sustainable manner. This community service activity aims to increase the understanding and awareness of grade III–IV elementary school children towards sorting organic and inorganic waste through a game-based learning approach. The activity was carried out in the Bojongsari area, Depok, involving 10 children as participants. The methods used include delivering interactive material, waste sorting competitions through the Eco-Race Little game, and making mini posters with environmental themes. The results of the activity showed that around 90% of participants were able to differentiate and sort organic and inorganic waste correctly. Apart from increasing cognitive understanding, this activity also fosters an attitude of cooperation, creativity and concern for the environment. Thus, the Little Eco-Race activity is considered effective as a fun and applicable environmental education model for elementary school age children.